Wicca in the 21st Century: The Evolution of a Faith - Frost, Guy (New Age Movements, Occultism, and Spiritualism Research Library, 2017)
Guy Frost to come speak at the 33rd Annual Retreat in 2017. This PowerPoint discusses Wicca and how it has evolved in the 21st century. Although not stated specifically, many of these changes reflect Neowiccan views. This presentation has useful notes. This digital asset was authorized by Guy Frost for inclusion in the New Age Movements, Occultism, and Spiritualism Research Library at Valdosta State University, Archives & Special Collections.
1 Electronic records. 1 PDF/A file and copies. 131 pages. 1.19 MB, 1245584 bytes.
Keywords: Electronic records; Wicca--History; Wicca--21st Century; Neowicca; Rowan Tree Church. Annual Retreat (33rd : 2017 : Kirkland, Wash.)